Tailoring design development and ideation in catering to industry demands / Fadila Mohd Yusof ...[et al.] - Mohd Yusof, Fadila; Mamat Nawi, Azmir; Md Hashim, Azhari; Ahmad Zamri, Ahmad Fazlan; Ab Hamid, Abu Hanifa; Azizan, Hasnul Azwan (UiTM Press, 2017)
Design development is one of the processes in the teaching and learning of industrial design. This process is important during the early stage of ideas before continuing to the next design stage. This study was conducted to investigate the comparison between academic syllabus and industry practices whether these processes are highly dependent on the idea generation and interaction related to the designer or to the student itself. The data were gathered through an observation of industry practice during conceptual design phase, teaching and learning process in academic through Video Protocol Analysis (VPA) method and interviews with industry practitioners via structured and unstructured questionnaires. The data were analysed by using NVivo software in order to formulate the results. The findings may possibly contribute to the teaching and learning processes especially in the improvement of industrial design syllabus in order to meet the industry demands.